Does School Type Matter in Academic Achievement in Regional Examination? Comparative Study of Private and Government Schools in Dessie Administrative Town, North Central Ethiopia - Eshetu, Amogne Asfaw (EDUCARE, 2015)
ABSTRACT: Academic achievement is a cumulative outcome of different factors. School type has a paramount effect on studentsâ performance in regional examination. This study was conducted to critically examine the effect of school type on students result in regional examination. An ex-post facto research design was employed to look into the impacts of school type on academic achievement in regional examination. Data analyses were undertaken using chi-square test, t-test, and ANOVA (Analysis of Variance). Independent sample t-test was used to test mean differences between private and government schools. ANOVA test was used to analyze mean differences based on level of satisfaction in school services. Chi-square test was used to see associations between school types with facilities and activities. Key informant interview and observation were also undertaken to substantiate the quantitative results. The t-test results revealed that private schools have scored statistically better than government ones. Students from private schools were highly satisfied with their school services. Private schools were found better equipped in library and laboratory facilities than government schools. Student centered method of teaching and tutorial classes have been more applied in private schools. Parentsâ involvement in school related affairs were better in private schools. Based on the findings, the recommendations that experience sharing between private and government schools as well as among schools should be organized by Dessie town administration educational office. More effort has to been done by concerned bodies so as to narrow the performance gab between private and government schools. In addition, government schools should be equipped with facilities as of the private schools.KEY WORDS: Academic achievement, regional examination, private/government schools, school services, library and laboratory facilities, and method of teaching and tutorial classes.About the Author: Amogne Asfaw Eshetu is a Lecturer at the Department of Geography and Environmental Studies WU (Wollo University), Dessie, P.O. Box 1145, North Central Ethiopia. For academic interests, the author can be contacted via phone at: +251913423595 or via e-mail at: amuvenu@yahoo.comHow to cite this article? Eshetu, Amogne Asfaw. (2015). âDoes School Type Matter in Academic Achievement in Regional Examination? Comparative Study of Private and Government Schools in Dessie Administrative Town, North Central Ethiopiaâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.161-170. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (December 5, 2014); Revised (January 15, 2015); and Published (February 28, 2015).